The Effect of Green Technology Implementation, Agricultural Product Innovation, and Green Technology Infrastructure Investment on Local Economic Growth in West Java - Judijanto, Loso; Suparwata, Dewa Oka; Cahya, Darmawan Listya; Widodo, Imam (West Science Nature and Technology, 2024)
This study examines the effects of green technology implementation, agricultural product innovation, and green technology infrastructure investment on local economic growth in West Java. Utilizing a quantitative approach, data were collected from 120 respondents using a Likert scale and analyzed through Structural Equation Modeling-Partial Least Squares (SEM-PLS 3). The findings reveal that green technology implementation, agricultural product innovation, and green technology infrastructure investment all significantly and positively impact local economic growth. The results emphasize the importance of sustainable practices and innovation in fostering economic development. The study provides insights for policymakers and business leaders to promote green technology adoption, support agricultural innovation, and invest in infrastructure to drive sustainable economic growth. Future research should explore additional variables and broader geographical contexts to enhance the model's explanatory power.